Recent advances in the diagnosis of dermatophytosis. (31st January 2020) - Begum, Jubeda; Mir, Nasir A.; Lingaraju, Madhu C.; Buyamayum, Bidyarani; Dev, Kapil
Abstract: Dermatophytosis is a disease of global significance caused by pathogenic keratinolytic fungi called dermatophytes in both animals and humans. The recent taxonomy of dermatophytes classifies them into six pathogenic genera, namely Microsporum, Trichophyton, Epidermophyton, Nannizzia, Lophophyton and Arthroderma . It is because of the delayed diagnostic nature and low accuracy of dermatophyte detection by conventional methods that paved the path for the evolution of molecular diagnostic techniques, which provide the accurate and rapid diagnosis of dermatophytosis for an appropriate, timely antifungal therapy that prevents the nonspecific over‐the‐counter self‐medication. This review focuses on the importance of rapid and accurate diagnosis of dermatophytosis, limitations of conventional methods, selection of targets in diagnosis, and factors affecting sensitivity and specificity of various molecular diagnostic technologies in the diagnosis of dermatophytosis. Generally, all the molecular techniques have a significant edge over the conventional methods of culture and microscopy in the dermatophytosis diagnosis. However, in mycology laboratory, the suitability of any molecular diagnostic technique in the diagnosis of dermatophytosis is driven by the requirement of time, economy, complexity, the range of species spectrum detected and the scale of diagnostic output required. Thus, various choices involved in the pursuit of a diagnosis of dermatophytosis are determined by the available conditions and the facilities in the laboratory.